57.8k views
0 votes
For f(x)-3x+1 and g (x)-x^2-6 find (f•g)(x)

For f(x)-3x+1 and g (x)-x^2-6 find (f•g)(x)-example-1

2 Answers

6 votes

the correct Answer is

3x^3+x^2-18x-6

User Ask About Monica
by
5.1k points
4 votes

Answer & Step-by-step explanation:

For this problem, all we have to do is multiply the two expressions.

f(x) = 3x + 1

g(x) = x² - 6

Now, let's set up our equation for multiplication.

(f * g)(x) = (3x + 1)(x² - 6)

(f * g)(x) = 3x³ - 18x + x² - 6

(f * g)(x) = 3x³ + x² - 18x - 6

So, (f * g)(x) is 3x^3 + x^2 - 18x - 6

User Khalil Khalaf
by
5.3k points